Iliotibial Band Syndrome (ITBS) – Etiology, Diagnosis and Physiotherapeutic Management. A Literature Review - Mliczek, Aleksandra; Roczyński, Brajan; Polok, Izabela (Quality in Sport, 2026)
Background: Iliotibial band syndrome (ITBS) is a leading cause of lateral knee pain in endurance athletes, with an incidence of 5-14% among runners. Long regarded as a "friction syndrome" caused by the band sliding over the lateral femoral epicondyle, this model has been increasingly challenged by anatomical and imaging studies, with direct consequences for clinical management. Aim: To systematize current knowledge on the etiology, clinical presentation, diagnosis and therapeutic management of iliotibial band syndrome, based on available literature. Material and methods: A narrative review was conducted based on original studies, systematic reviews and clinical overviews addressing the anatomy, biomechanics, etiology, diagnosis, and conservative and surgical management of ITBS. Results: Cadaveric and imaging studies show the band is firmly tethered to the femur, contradicting the friction theory and supporting a compression-based mechanism affecting an innervated fat pad. ITBS is an overuse injury linked to training errors, altered hip/knee kinematics and hip abductor weakness, though causality for the latter remains unresolved. Diagnosis is mainly clinical, based on history and tenderness over the epicondyle, with the Noble and Ober tests as supportive tools; MRI and ultrasound are reserved for atypical cases. Management progresses from relative rest, through hip- and kinetic-chain physiotherapy as the mainstay, to physical modalities and, rarely, injection or surgery. Conclusions: Understanding of ITBS has shifted from a friction- to a compression-based model, favoring hip and kinetic-chain strengthening over ITB stretching. Diagnosis remains clinical, with imaging as confirmatory. The causal role of hip weakness, inconsistent biomechanical findings, and the relevance of distal structures like the gastrocnemius warrant further research.